Mosquito-Borne Viral Infections in the Krasnodar Territory ~ Risks of Autochthonous Cases of the Disease - S. V. Lenshin; I. V. Patraman; S. V. Alkhovsky; O. I. Vyshemirsky (Эпидемиология и вакцинопрофилактика)
Introduction. Global climate changes affect the habitats of insects, including mosquitoes, which are carriers of dangerous natural focal infections. When mosquitos develop new territories, they create a potential threat to people who find themselves in these areas. In the Krasnodar Region, a stable population of Ae. albopictus mosquitoes was formed in the 21st century. These mosquitoes are carriers of many viral pyrrhoid-focal infections, such as Dengue, Chikungunya, Zika fever and Yellow fever. Estimations of biological, epidemiological and cultural data can help to answer the question of the probability of occurrence of autochthonous cases of infection.Aim. To estimate the probability of occurrence of autochthonous cases of viral infections carried by Ae. albopictus mosquitoes on the territory of the Black Sea coast of the Krasnodar territory. For the review, we used scientific publications describing the occurrence of autochthonous diseases in similar climate zones inhabited by Ae. albopictus mosquitoes, the biology of these mosquitoes, as well as official reports of the sanitary services of Europe and the Russian Federation. A stable population of Ae. albopictus mosquitoes has formed on the Black Sea coast of the Krasnodar Territory. The local climate, including the temperature range is favourable for active reproduction of vectors and autochthonous transmission of viral infection.Conclusion. Despite the favourable conditions for the release of mosquitoes and the formation of a stable population, autochthonous transmission requires the introduction of the source of infection during the viremia period to infect the mosquito population. In recent years, isolated cases of such drifts have been reported in the Krasnodar Territory, which indicates a low probability of local cases of transmission. However, with the development of the tourism sector, the flow of tourists from endemic areas will inevitably increase. In addition, the increase in the well-being of the population, trips to these countries will become more frequent this may well increase the risk of transmission of viral infections by local mosquitoes. In any case, the weakening of epidemic control of mosquitoes and medical surveillance of imported cases of tropical fevers will have serious consequences.